2007
DOI: 10.1002/cne.21486
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin‐immunoreactive axon terminals innervate pyramidal cells and interneurons in the rat basolateral amygdala

Abstract: The basolateral nuclear complex of the amygdala (BLC) receives a dense serotonergic innervation that appears to play a critical role in the regulation of mood and anxiety. However, little is known about how serotonergic inputs interface with different neuronal subpopulations in this region. To address this question, dual-labeling immunohistochemical techniques were used at the light and electron microscopic levels to examine inputs from serotonin-immunoreactive (5-HT+) terminals to different neuronal subpopula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
75
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 110 publications
(150 reference statements)
11
75
0
Order By: Relevance
“…However, when serial electron microscopic reconstructions are examined, 5-HT terminal boutons make synaptic contacts in several structures (Descarries et al, 2010). Present observations indicated that a sizable contingent of 5-HT terminals make synaptic junctions in the lateral amygdala, in agreement with previous ultrastructural analysis in the rat lateral amygdala (Muller et al, 2007). Unexpectedly, in Pet1 knock-out mice, we found an increased proportion of synaptic junctions made by the spared 5-HT axon terminals in the amygdala, thalamus, and hypothalamus.…”
Section: Pet1-resistant 5-ht Neurons Define a Subsystem Embedded In Tsupporting
confidence: 89%
See 1 more Smart Citation
“…However, when serial electron microscopic reconstructions are examined, 5-HT terminal boutons make synaptic contacts in several structures (Descarries et al, 2010). Present observations indicated that a sizable contingent of 5-HT terminals make synaptic junctions in the lateral amygdala, in agreement with previous ultrastructural analysis in the rat lateral amygdala (Muller et al, 2007). Unexpectedly, in Pet1 knock-out mice, we found an increased proportion of synaptic junctions made by the spared 5-HT axon terminals in the amygdala, thalamus, and hypothalamus.…”
Section: Pet1-resistant 5-ht Neurons Define a Subsystem Embedded In Tsupporting
confidence: 89%
“…The 5-HT receptors that are present in the areas where 5-HT axon terminals remain in Pet1 knock-out mice may provide interesting clues in this respect. For instance, in the BLA, where 5-HT boutons form synapses, 5-HT2A, 5-HT2C, and 5-HT3 receptors are the main receptors (Wright et al, 1995;McDonald and Mascagni, 2007;Muller et al, 2007). 5-HT2A and 5-HT2C receptors are also strongly expressed in the hypothalamic paraventricular nucleus and intralaminar thalamic nuclei, with preserved innervation in the Pet1 knock-out (Zhang et al, 2002;Heisler et al, 2007).…”
Section: Pet1-resistant 5-ht Neurons Define a Subsystem Embedded In Tmentioning
confidence: 99%
“…Amygdala GABAergic interneurons are targets of dopamine, NE, serotonin, acetylcholine, and cannabinoids (Brinley-Reed and McDonald, 1999;Rainnie, 1999;Katona et al, 2001;McDonald and Mascagni, 2001;Azad et al, 2003;Bissiere et al, 2003;Kroner et al, 2005;Muller et al, 2007Muller et al, , 2011Tully et al, 2007;Pinard et al, 2008). Repeated stress may influence amygdala GABAergic transmission by impairing the neuromodulation of amygdala neurons (Braga et al, 2004;Buffalari and Grace, 2009;Hill et al, 2009Hill et al, , 2010, perhaps in an age-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…The highest density of serotonin-IR fibers is observed in the magnocellular division of the basal nucleus and amygdalohippocampal area (Steinbusch 1981). On the other hand, in the monkey's amygdala, the density of serotonin-IR terminals is as follows: (i) low in the accessory basal, anterior cortical, posterior cortical and medial nuclei, and in subregions of the periamygdaloid cortex; (ii) moderate in portions of the basal, lateral, and intercalated nuclei; and (iii) high in the central nucleus, the nucleus of the lateral olfactory tract, the paralaminar nucleus, the anterior amygdaloid area, and a small region of the amygdalohippocampal area (Bauman and Amaral 2005 (Muller et al 2007b). …”
Section: Serotonergic Innervation Of Amygdala and Hippocampal Regionmentioning
confidence: 99%
“…In the amygdala and hippocampal region, serotonin operates via conventional synapses as well as local volume neurotransmission, reaching their specific receptors through extra-cellular or paracrine diffusion (Amaral and Lavenex 2007;Muller et al 2007b). …”
Section: Serotonergic Innervation Of Amygdala and Hippocampal Regionmentioning
confidence: 99%